Controlling the morphology of solution-processed CuIn(SSe)2 absorber layers by film thickness and annealing temperature. (12th August 2020) - Do, Quyen; Manh, Nguyen The; Triet, Luong Nguyen Dai; Choi, Yura; Lee, Young-Woo; Cho, Yonghyun; Lee, Kwang Jae; Cho, Namchul
Abstract: We demonstrated the solution-processed CuIn(S, Se)2 solar cells using a diamine/dithiol cosolvent. Compared to the traditional CIGS materials made with the Selenization process, we fabricated CISSe films without the Selenization process. The crystallinity, optical properties, and morphology of the CIGSSe films were changed by annealing temperature and film thickness. The band gap energy were found approximately 1.5 eV with the different film thickness.